The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/polym10101049
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of DOPO-ITA Modified Ethyl Cellulose and Its Application in Phenolic Foams

Abstract: In order to improve the performance of phenolic foam, an additive compound of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and Itaconic acid (ITA) were attached on the backbone of ethyl cellulose (EC) and obtained DOPO-ITA modified EC (DIMEC), which was used to modify phenolic resin and composite phenolic foams (CPFs). The structures of DOPO-ITA were verified by Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance (1H NMR). The molecular structure and microstructure were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…The specific strength [ 1 , 2 , 3 , 4 , 5 ] and dimensional stability of foaming materials [ 6 ] are directly related to cell density, which is determined by the number of cells present during the foaming process. Therefore, the quality of foaming materials can be effectively improved by regulating nucleation in the foaming process [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The specific strength [ 1 , 2 , 3 , 4 , 5 ] and dimensional stability of foaming materials [ 6 ] are directly related to cell density, which is determined by the number of cells present during the foaming process. Therefore, the quality of foaming materials can be effectively improved by regulating nucleation in the foaming process [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carvalh, G. et al [18], Li, J.; Wang, W. et al [19], Li, J. and Zhang, J. et al [20] all used a lignin moiety to replace the phenol with formaldehyde to form a phenolic resin to increase its viscosity, reduce formaldehyde emissions, and increase the strength of the phenolic foam. Ma, Y. et al introduced DOPO-ITA into the phenolic resin to improve the residual carbon and the cell distribution [21]. Turunen, M. et al used starch, urea and lignin as the phenolic resin modifiers to change the methylene bridge content of the resin by changing the molar mass ratio [22].…”
Section: Introductionmentioning
confidence: 99%
“…10), the toughness of DCMPFs was fail. Therefore, the ratio of mass was increased [30]. The results showed that the content of DOPO-g-CNSL/P was not too much, the better dosage of DOPO-g-CNSL/P was no more than 10%.…”
Section: Fragility Of Dcmpfsmentioning
confidence: 97%
“…4. For DOPO, the signal around 6.56 to 8.86 ppm was corresponded to the phenyl protons [28][29][30][31]. For CNSL, the chemical shifts of H a , H b , H c , H d and H e were observed at 0.97 ppm, 1.38 ppm, 2.10 ppm, 1.64 ppm and 2.60 ppm respectively, and the signal around 5.44 ppm (H f ) was corresponded to double bonds protons [10].…”
Section: H Nmr Of Dopo-g-cnslmentioning
confidence: 99%